The influence of borehole arrangement of soundless cracking demolition agents (SCDAs) on weakening the hard rock - Tang, Wei; Zhai, Cheng; Xu, Jizhao; Sun, Yong; Cong, Yuzhou; Zheng, Yangfeng (International journal of mining science and technology, 2021)
The hard roof difficult to collapse easily causes gas accumulation, which threatens the production safety of coal mine. Therefore, roof pre-cracking is required. Although blasting and hydraulic fracturing can also crack the roof, blasting can easily induce rock bursts, whereas hydraulic fracturing needs complex equipment. In contrast, soundless cracking demolition agents (SCDAs) with noise-free, dust-free, and safe characteristics have obvious advantages. The main component of SCDA is calcium oxide, which reacts with water to produce higher expansion pressure. In this paper, focused on the angles of the borehole, the effect of SCDA is analyzed by numerical simulation based on Pingdingshan coal mine. The research results showed that the azimuthal angle α (between borehole projection and the roadway direction) does not significantly affect the efficacy of SCDAs, whereas the influence of borehole elevation angle β is far more significant than that of the azimuthal angle. Therefore, the angle β is a dominant factor influencing the effect of SCDAs. Based on different effects of SCDAs at different angle of boreholes, the weakening unit was established, so the SCDAs could give full play to roof fracturing. Moreover, field tests validated the importance of borehole angle on weakening the hard roofs.